The role of case study in teaching english to journalists (Журналистика сериясы, 2016)
The case study method has been widely used in education a learning vehicle with specific educational objectives in mind. It has been highly popular in many disciplines such as journalism, economics, law cases, psychiatry and engineering, where the skills of unstructured and complex problem solving are involved. Case studies provide students with the op-portunity of reading, understanding and discussing a specific problem area. Students are expected to propose logical solutions to the problem presented. Each case is written to leave the student at a decision point with the manager in the case confronted. It will usually describe how the current position developed and what problems key personalities in the case are currently facing. Tables of data, diagrams and photographs may be added to help provide a more complete picture.